Students’ Views on Learning English Speaking at SMP Negeri 1 Demak - Nabihah, Insyira; Mulyadi, Dodi; Aimah, Siti (UM Purwokerto Press, 2025)
This study examines how students at SMP Negeri 1 Demak perceive learning English in class, as they recognize the importance of being able to speak English in today's global and connected world. Many students know that learning English is important for their future. Still, when they are asked to speak English in class, they often feel anxious and unsure of themselves, especially when they fear making mistakes and being judged. This is a common problem in middle schools because students don't get to talk much. This study used a quantitative data method with 40 students from grades VII to IX as participants. The data was collected through open-ended questionnaires that asked students about their challenges, preferences, and suggestions. The results reveal that students are more likely to speak up when the classroom is calm and friendly. They like to learn when it's fun, like making videos, playing games, or talking to friends. Students think that it is very important for their professors to talk to them and give them emotional support in class so that they feel safer. Teachers should be kinder, tell their kids the truth, and allow them to participate without being afraid of making mistakes. Changing the way they teach might help teachers and students who are nervous about speaking. This will assist kids learn how to talk to each other better, which is a skill that is very vital in the 21st century.